Theorizing rituals / Vol. 1 Issues, topics, approaches, concepts / Jens Kreinath; Jan Snoek ... (ed.) - Kreinath, Jens; Snoek, Joannes A. M. (Theorizing rituals, 2006)
Intro -- CONTENTS -- PREFACE AND ACKNOWLEDGMENTS -- RITUAL STUDIES, RITUAL THEORY, THEORIZING RITUALS-AN INTRODUCTORY ESSAY* -- PART ONE: METHODOLOGICAL AND METATHEORETICAL ISSUES -- DEFINING 'RITUALS' -- RITUAL AND OTHER FORMS OF SOCIAL ACTION -- CONCEPTUAL ALTERNATIVES TO 'RITUAL' -- 'RITUAL': A LEXICOGRAPHIC SURVEY OF SOME RELATED TERMS FROM AN EMIC PERSPECTIVE -- PART TWO: CLASSICAL TOPICS REVISITED -- MYTH AND RITUAL -- RITUAL AND PSYCHE -- RITUAL IN SOCIETY -- RITUAL: RELIGIOUS AND SECULAR -- STRUCTURE, PROCESS, FORM -- RITUAL AND MEANING -- PART THREE: THEORETICAL APPROACHES -- ACTION -- AESTHETICS -- COGNITION -- COMMUNICATION -- ETHOLOGY -- GENDER -- PERFORMANCE -- PRAXIS -- RELATIONALITY -- SEMIOTICS -- PART FOUR: PARADIGMATIC CONCEPTS -- AGENCY -- COMPLEXITY -- DEFERENCE -- DYNAMICS -- EFFICACY -- EMBODIMENT -- EMOTION -- FRAMING -- LANGUAGE -- MEDIA -- PARTICIPATION -- REFLEXIVITY -- RHETORICS -- TRANSMISSION -- VIRTUALITY -- PART V: EPILOGUE -- AN INVITATION TO 'THEORIZING' THEORIZING RITUALS: SOME SUGGESTIONS FOR USING THE INDEXES -- INDEX OF NAMES -- INDEX OF SUBJECTS -- REFERENCES.